Increasing Coral Reef Resilience Through Successive Marine Heatwaves. Issue 17 (30th August 2021) - Fox, Michael D.; Cohen, Anne L.; Rotjan, Randi D.; Mangubhai, Sangeeta; Sandin, Stuart A.; Smith, Jennifer E.; Thorrold, Simon R.; Dissly, Laura; Mollica, Nathan R.; Obura, David
Abstract: Ocean warming is causing declines of coral reefs globally, raising critical questions about the potential for corals to adapt. In the central equatorial Pacific, reefs persisting through recurrent El Niño heatwaves hold important clues. Using an 18‐year record of coral cover spanning three major bleaching events, we show that the impact of thermal stress on coral mortality within the Phoenix Islands Protected Area (PIPA) has lessened over time. Disproportionate survival of extreme thermal stress during the 2009–2010 and 2015–2016 heatwaves, relative to that in 2002–2003, suggests that selective mortality through successive heatwaves may help shape coral community responses to future warming. Identifying and facilitating the conditions under which coral survival and recovery can keep pace with rates of warming are essential first steps toward successful stewardship of coral reefs under 21st century climate change. Plain Language Summary: Mass bleaching events caused by warming oceans and intensifying marine heatwaves have killed millions of corals globally. In the central equatorial Pacific, coral reefs experienced three extreme heatwaves within 15 years, providing valuable insights into the mechanisms that could facilitate coral survival under global warming. We examined an 18‐year record of coral cover in the Phoenix Islands Protected Area (PIPA) to track the community response to each event. In the 2002/2003 heatwave, coral communities across PIPA were decimated, with some reefs experiencing near complete mortality. Strong recovery followed and in 2009/2010, a heatwave of similar magnitude caused minimal mortality. The 2015/2016 heatwave was the strongest on record, exposing PIPA's coral communities to twice the thermal stress of 2002/2003. Yet coral mortality during this event was disproportionately low. An examination of 11 environmental metrics that may have modulated the impacts of extreme heat revealed no consistent explanation. Rather, our results support the hypothesis that the survival of thermally tolerant colonies in 2002/2003 and localized recruitment, facilitated recovered communities with greater thermal tolerance than those that inhabited the reefs two decades ago. Understanding and promoting the conditions that facilitate coral recovery and adaptation would enhance our ability to foster coral reef survival. Key Points: An 18‐year record of coral cover spanning three strong El Niño heatwaves reveals a weakening impact of thermal stress over time Coral communities recovered from the catastrophic 2002/2003 heatwave suffered lower mortality in 2015/2016 despite a doubling of thermal stress A decoupling of coral mortality and thermal stress suggests repopulation by thermally tolerant survivors may aid adaptation to ocean warming